PENANGANAN PEKERJA MIGRAN DI MALAYSIA - Suradji Suradji (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
Economic crisis has led the government to a dilemmatic situation. On one hand, the government is demanded to provide and/or expand work opportunities, especially for those laid off due to the crisis. On the other hand, the government has limitations to fulfill the demands. One way to solving this problem is sending labors overseas, particularly to Malaysia. Despite that, the policy poses some problems. Empirical facts show there are a lot of problems concerning Indonesian migrant workers: illegal status, unjust treatment before the law, and massive deportation. These problems arise due to the absence of sufficient regulations protecting the workers. In addition, overlapped coordination among agencies as well as weak control over the matter worsens the situation. For that reason, the current procedures should be rearranged and bilateral relations between the Indonesian and Malaysian governments should be tightened in the field of manpower, particularly to safeguard Indonesian workers’ rights.